EFFECTIVE USE OF TECHNOLOGY IN FOOTBALL: EFFECTIVE USE OF TECHNOLOGY IN FOOTBALL - Hasanov, anvar (Физическое воспитание, спорт и здоровье, 2025)
In order to increase the effectiveness of training sessions, effective methods of introducing new technologies in football training are discussed.